PENGARUH BRAND AWARENESS, BRAND AMBASSADOR, DAN WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN - Fitriana, Siti Afin Nur; Nugroho, Dian Ari (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
Online media is the choice as a means of promotion considering the number of internet users is increasing all the time. Business people have to think about how to survive and continue to grow in the midst of crowded competitors. This study aims to determine the effect of brand awareness, brand ambassador and word of mouth on purchasing decisions. This type of research uses survey research to determine the effect of the variables in this study. The population used in this study were Renkli.co consumers. The sampling technique in this research is the saturated sample, namely the number of samples is the same as the total population of 110 respondents. Sampling data obtained through questionnaires were processed using multiple linear regression analysis with the help of SPSS version 25 software. The results of this study indicate that brand awareness have a positive and significant effect on purchasing decisions. Brand ambassadors have a positive and significant effect on purchasing decisions. Word of mouth have a positive and significant effect on purchasing decisions.